2017
DOI: 10.1016/j.chest.2016.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation After Lung Transplantation

Abstract: IntroductionTo explore the hypothesis that early ventilation strategies influence clinical outcomes in lung transplantation, we have examined our routine ventilation practices in terms of tidal volumes (Vt) and inflation pressures.Methods 124 bilateral lung transplants between 2010 and 2013 were retrospectively assigned to low (<6ml/kg), medium (6-8ml/kg) and high (>8ml/kg) Vt groups based on ventilation characteristics during the first 6 hours after surgery. Those same 124 patients were also stratified to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In the present study, the animals remained hemodynamically stable, regardless of the PEEP administered, with all groups showing similar heart rate, perfusion, and lactate levels, data similar to those of the literature (4,7,13).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the animals remained hemodynamically stable, regardless of the PEEP administered, with all groups showing similar heart rate, perfusion, and lactate levels, data similar to those of the literature (4,7,13).…”
Section: Discussionsupporting
confidence: 91%
“…The patients ventilated using volume-control were divided into low tidal volumes o 6 mL/kg, medium tidal volumes between 6 to 8 mL/kg, and high tidal volumes 4 8 mL/kg, and the authors found that in both the volume-and pressure-control patients, the only factor that predicted pulmonary complications after transplantation was high inflation pressures, defined as a PIP Z 25 mmH 2 O in patients receiving pressure-control ventilation and a plateau pressure Z 25 mmH 2 O in patients receiving volume-control ventilation. 17 As long as the plateau pressure remained o25 mmH 2 O, the incidence of pulmonary complications did not increase with increasing tidal volumes. Verbeek et al randomly assigned patients undergoing double lung transplantation to a control group that received volume-controlled ventilation with 5 cmH 2 O of PEEP and low tidal volumes (6 mL/kg for two lung ventilation and 4 mL/kg for one lung ventilation) or an alveolar recruitment group who were ventilated using pressure controlled ventilation at 16 cmH 2 O with 10 cmH 2 O of PEEP and a stepwise PEEP-based alveolar recruitment algorithm, with the final outcome being the arterial oxygen/inspired oxygen ratio 24 hours after the first lung was reperfused.…”
mentioning
confidence: 83%
“…One strategy is the use of volume-controlled ventilation with tidal volumes set at 6 mL/kg of the donor weight, with 5 to 10 cmH 2 O of PEEP, and a goal of keeping the peak airway pressures o30 mmHg; however, the use of pressure-control ventilation is becoming more prevalent. Thakuria et al 17 compared the records of patients who had undergone double lung transplantation, the strategies used to ventilate them, and the patient outcomes and found that the majority of patients were ventilated using a pressure-control mode. The patients ventilated using volume-control were divided into low tidal volumes o 6 mL/kg, medium tidal volumes between 6 to 8 mL/kg, and high tidal volumes 4 8 mL/kg, and the authors found that in both the volume-and pressure-control patients, the only factor that predicted pulmonary complications after transplantation was high inflation pressures, defined as a PIP Z 25 mmH 2 O in patients receiving pressure-control ventilation and a plateau pressure Z 25 mmH 2 O in patients receiving volume-control ventilation.…”
mentioning
confidence: 99%
“…It also calls for ongoing critical appraisal of our management goals and for constant quality improvement to understand and exploit new strategies to reduce complications, to enhance patient's perioperative journey and to improve both short-and long-term survival of lung transplant recipients. [13][14][15][16][17][18] This redefined role has major implications for our specialties in pushing the boundaries of super specialization in transplant anesthesia and intensive care and also with regard to closer team working with the surgical and respiratory teams from the time of patient listing through the transplant operation and postoperative ICU stay. 19,20 Building a consensus framework These worldwide trends have been considered by the Transplant Subcommittee of the European Association of Cardiothoracic Anesthetists (EACTA), which represents a distinctive international subspecialty group of cardiothoracic anesthetists and critical care physicians delivering perioperative care for lung transplants recipients.…”
Section: Lung Transplantation (Ltx) Is An Established Therapy With Major Current Limitationsmentioning
confidence: 99%